2019
DOI: 10.7567/1347-4065/ab0ba9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic preload control of traveling wave rotary ultrasonic motors for energy efficient operation

Abstract: Ultrasonic motors (USM) have great potential to become the actuators of the next generation. However, the current control schemes of USM are still suffering from some shortcomings including limitation of output speed and torque range, and excessive heat generation. Driving schemes based solely on frequency control suffer from reduced efficiencies across most of its operation band due to having a single optimum driving frequency around resonance. In this paper, the effect of preload on USM driving characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Zhang et.al [ 20 ] developed the Dahl model to avoid discontinuities of contact forces in both left and right directions of motion for V-shape linear ultrasonic motors. In addition, the dead zone [ 21 ], wear of the friction interface [ 22 ], and change of pre-pressure [ 23 ] are also frequently related to contact friction [ 24 ]. The friction exacerbates the nonlinearity of the vibration of the stator in an ultrasonic motor, which has led to more complex nonlinear dynamics and has further complicated the nonlinear problems of TRUM as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et.al [ 20 ] developed the Dahl model to avoid discontinuities of contact forces in both left and right directions of motion for V-shape linear ultrasonic motors. In addition, the dead zone [ 21 ], wear of the friction interface [ 22 ], and change of pre-pressure [ 23 ] are also frequently related to contact friction [ 24 ]. The friction exacerbates the nonlinearity of the vibration of the stator in an ultrasonic motor, which has led to more complex nonlinear dynamics and has further complicated the nonlinear problems of TRUM as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…In order to track and control the optimal efficiency of the TRUM (Traveling-wave Rotary Ultrasonic Motor), Mustafa [16] used the preload dynamic loading mechanism to achieve efficient and stable tracking. Another of Mustafa's papers [17] analyzed the influence of preload on the driving characteristics and showed that the preload would affect the driving efficiency, resonant frequency, and output power range. Based on the frequency control of the ultrasonic motor, he used the dynamic preloading mechanism as the auxiliary controller, which improved the driving efficiency and expanded the range of output power.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the generation of the elliptical motion is significant for piezoelectric transducers. However, for producing the elliptical motion, two vibration modes are generally required to be stimulated and coupled in the piezoelectric transducers, increasing the difficulties of design, manufacturing, and assembling of transducer [5,6]. Additionally, how to achieve the resonant frequency consistency of the two selected vibration modes is also a difficult issue.…”
Section: Introductionmentioning
confidence: 99%